Eucalipto e ectomicorrizas para fitorremediação de solos contaminados com zinco - Weirich, Sidinei Wolnei (2013)
Population growth, human technological development and intensification of human activities on the environment, has generated considerable volumes of industrial, agricultural and urban waste, which when applied to the soil can contaminate it with heavy metals, including zinc (Zn). To the be present in high concentrations in the soil this element is phytotoxic to most crops, disabling growing areas, becoming a risk to human health and the environment. Zn contaminated areas need to be recovered. To this end, this study aimed to evaluate the growing of E. grandis, C. citriodora, E. saligna and E. dunnii, and the effect of isolated ectomycorrhizal association with the development of eucalyptus on soil contaminated by Zn. To do this, set up an experiment to evaluate the growth of seedlings of E. grandis, C. citriodora, E. saligna and E. dunnii in soil contaminated by zinc. In another experiment sequence was conducted to assess the effect of ectomycorrhizal isolates of Pisolithus microcarpus (UFSC-Pt116), Pisolithus tinctorius (UFSC-132) and isolated UFSC-121 in seedling development of E. grandis, C. citriodora, E. saligna and E. dunnii. Finally, we assessed the development of seedlings of C. citriodora and the effect of inoculation with Pisolithus microcarpus (UFSC-Pt116) in soil contaminated with Zn. C. citriodora has greater plant height, main root length, root volume, dry mass of cauline aste, leaf dry weight, root dry mass and total dry mass than E. grandis, E. saligna and E. dunnii in soil contaminated with 980 mg kg-1 Zn. C. citriodora, was the fastest-growing species in the soil with 79% clay contaminated by the addition of 980 mg kg-1 Zn. While E. dunnii had development of vegetative parts significantly reduced at this dose. Inoculation of isolated Pisolithus microcarpus (UFSC-Pt116) in eucalyptus species yielded the highest percentage of colonized roots in C. citriodora. The percentage of ectomycorrhizal colonization of Pisolithus microcarpus (UFSC-Pt116) in C. citriodora was stimulated by the addition to 1,412.21 mg kg-1 Zn in solo. The addition of 1,500 mg kg-1 Zn in soil with 81% clay does not affect the development of C. citriodora.